1997
DOI: 10.1046/j.1365-2796.1997.94101000.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term insulin‐like growth factor‐I or growth hormone treatment on bone turnover, renal phosphate reabsorption and 1,25 dihydroxyvitamin D3 production in healthy man

Abstract: Objectives. To find out whether insulin‐like growth factor‐I (IGF‐I) mimics the stimulatory effects of growth hormone (GH) on bone turnover and renal tubular phosphate reabsorption. Design. Randomized, crossover study. Setting. University Hospital, Zürich, Switzerland. Subjects. Seven young healthy male subjects. Interventions. Each subject was studied three times at 2‐week intervals, treated with saline 0.9% (S), IGF‐I [8 μg kg−1 h−1] by a continuous subcutaneous infusion and finally with GH (6 U. twice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 33 publications
2
60
0
4
Order By: Relevance
“…Deficiency in IGF1, a prominent member of IGFs, is suggested to be a cause of decrease in bone density with aging (20,21), and administration of IGF1 prevents the decrease of bone density in osteoporosis patients in part by stimulating osteogenesis (22)(23)(24). The high homology between IGF1 and insulin suggested that the osteogenesis-enhancing activity of IGF1 may be mimicked by the chemicals that potentiated the insulin-induced adipogenesis.…”
Section: Figmentioning
confidence: 99%
“…Deficiency in IGF1, a prominent member of IGFs, is suggested to be a cause of decrease in bone density with aging (20,21), and administration of IGF1 prevents the decrease of bone density in osteoporosis patients in part by stimulating osteogenesis (22)(23)(24). The high homology between IGF1 and insulin suggested that the osteogenesis-enhancing activity of IGF1 may be mimicked by the chemicals that potentiated the insulin-induced adipogenesis.…”
Section: Figmentioning
confidence: 99%
“…It has long been known that insulin-like growth factor 1 (IGF1) causes an increase in the circulating levels of 1,25-dihydroxyvitamin D (1,25(OH) 2 D), the hormonally active vitamin D metabolite, by stimulating the expression and activity of the 1a-hydoxylase that produces 1,25(OH) 2 D in the kidney (1,2). Indeed, plasma 1,25(OH) 2 D is significantly higher in active than controlled acromegaly, with a tendency to hypercalcemia, hyperphosphatemia, and hypercalciuria (3).…”
Section: Introductionmentioning
confidence: 99%
“…Similar stimulatory effects were obtained when GH was administered for a short-time. Brixen et al showed a significant increase in total vitamin D in 20 normal male volunteers after just 7 days of treatment with a pharmacological dosage of GH [13], and GH infusions in 7 normal healthy male volunteers increased 1,25(OH)2-D3 levels within 36 h [14].…”
Section: Gh and Vitamin Dmentioning
confidence: 99%
“…Therefore, one potential mechanism by which GH stimulates increases in bone mass is via increases in IGF-I and consequently in [17]. Indeed, it is widely demonstrated that IGF-I causes an increase in the circulating levels of 1,25(OH)2-D3 by directly stimulating expression and activity of the 1α-hydoxylase that produces 1,25(OH)2-D3 in the kidney [14,18].…”
Section: Igf-i and Vitamin Dmentioning
confidence: 99%